Penyusunan Asesmen Kompetensi Minimum (AKM) Guru IPA dan Matematika Kabupaten Pesawaran - Nurhanurawati; Tina Yunarti; Viyanti; Nurain Suryadinata (Nuwo Abdimas, 2023)
-This community service activity aims to improve the abilities of mathematics and science teachers in Pesawaran Lampung Regency in compiling a Minimum Competency Assessment (AKM). The training was carried out in the microteaching laboratory at FKIP, University of Lampung. The participants in this activity were teachers who were members of the Mathematics MGMP and Science MGMP in the Pesawaran Regency, Lampung Province. The number of participants who took part in this activity was 30 people. The methods used in community service activities are lectures, workshops, and presentations. This activity results in an increase in the teacher's ability to make AKM questions according to their field of study. This is shown from the products produced by the teacher, namely in the form of AKM questions and also based on the results of the posttest at the end of the activity. In addition, the teachers involved also gave a positive response to the implementation of this activity